The Influence Of The Responsibility Sharia Supervisory Board, Sharia Compliance, Issuance Of Sharia Securities, And The Size Of The Board Of Commissioners On The Level Of Disclosure Of Islamic Social Reporting Islamic Bank In Indonesia - Yulistia Devi; Liya Ermawati; Okta Supriyaningsih; Diah Mukminatul Hasimi; Zhatu Restie Utamie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to test the effect of the responsibilities of the Sharia Supervisory Board, Sharia Compliance, issuance of Sharia securities, and the size of the Board of Commissioners on the level of disclosure of Islamic Social Reporting at Islamic Banks in Indonesia. This study used descriptive and correlational quantitative methods. The method of data collection is to use secondary data sources, and in terms of the way the data collection method in this study uses data collection techniques with documents in the form of annual financial statements and GCG reports. The data analysis method in this study uses descriptive statistics and classical assumption tests consisting of normality tests, multicollinearity tests, and heteroplasticity tests. The population in this study is Sharia Commercial Bank in Indonesia for the period 2016-2020 which amounted to 14 Islamic Banks. The sample determination technique was carried out using purposive sampling techniques with criteria: Sharia Commercial Bank which publishes annual reports and GCG reports and lists the results of GCG Self Assessment in 2016-2020, from these criteria, a sample of 13 Islamic Banks was obtained. The results of this study showed that partially the variables of the Responsibilities of the Sharia Supervisory Board, Sharia Compliance variables, and the Board of Commissioners Size variables had no effect on the ISR Disclosure Rate at Islamic Banks in Indonesia for the period 2016-2020, it can be concluded that H1, H2, and H4 were rejected. While on the variable issuance of Islamic securities shows that partially the Issuance of Sharia Securities affects the Level of ISR Disclosure at Islamic Banks in Indonesia for the period 2016-2020, it can be concluded that H3 is accepted. Simultaneously the variables of the Responsibilities of the Sharia Supervisory Board, Sharia Compliance, Issuance of Sharia Securities, and the Size of the Board of Commissioners have a significant effect on the Level of ISR Disclosure on Islamic Banks in Indonesia for the period 2016-2020, it can be concluded that H5 is accepted.